Interaction between social norms and animal welfare: a Malaysian legal perspective / Arif Fahmi Md Yusof - Md Yusof, Arif Fahmi (2014)
The law cannot be seen in isolation from the many factors which have led to its creation. The nature of law itself derives from many sources such as custom, religion and public practices which serve as social norms and social control. With respect to Malaysia, the present law itself develops from the interaction between many forces ranging from the customs and religion of its people, the influence of foreign colonization, and the internal political environment as well as public perspectives. Animal welfare law or laws relating to animals is no exception. It considers the practical link that it has with other disciplines which operate as social control such as philosophy, religion, politics and animal welfare sciences. By referring to doctrinal sources dealing with animal welfare law, and a fieldwork data from selected informants who deal with animal issues on a daily basis, this paper aims to examine the interactions between social norms and animal welfare in Malaysian legal perspective.